Taxonomy and systematics of the ‘Maharaja Barbs’ (Teleostei: Cyprinidae), with the description of a new genus and species from the Western Ghats, India - Katwate, Unmesh; Kumkar, Pradeep; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2020)
Maharaja Barbs (Teleostei: Cyprinidae), endemic to the high-altitude streams of the northern Western Ghats are currently represented by a single species, Puntius sahyadriensis. Integrative taxonomic analysis of these fishes reveals them to form a distinct clade within the Cyprinidae, for which we propose the name Waikhomia gen. nov. Waikhomia differs from Puntius and other closely related genera by a combination of characters including: barbels absent; last unbranched dorsal-fin ray smooth, with highly segmented apex; total vertebrae 30 (17 abdominal and 13 caudal); post-epiphysial fontanelle absent, frontals elongated, parietals narrow; infraorbital 2–4 large, deep and wide, overlapping cheek and preopercle; opercle not overlapping the interopercle laterally; free uroneural 2 absent; lateral line complete, with 23–25 perforated scales; pelvic fins jet black with tip of fins white; and body coloration consisting of multiple (6–8) spots and blotches on side of body. We also describe a new species of Waikhomia from the west-flowing Kali river system in the northern part of the Western Ghats, India. The new species, Waikhomia hira is distinguished from W. sahyadriensis by a combination of characters including a distinct body coloration, consisting of 7–8 small, rhomboidal spots arranged across the lateral-line scale row; 23–25 perforated lateral line scales; 10 pre-dorsal scales and 2–3 sparsely spaced gill rakers on epibranchial 1. Further, W. hira differs from its sister taxon, W. sahyadriensis, by a raw genetic distance ranging from 4.3–4.9% in partial cytochrome oxidase subunit 1, and 7.0–8.2% in partial cytochrome b genes.